PENGARUH STRUKTUR MODAL TERHADAP PROFITABILITAS PADA PERUSAHAAN LQ-45 YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2011-2015 - Mohammad Aryo Arifin (Universitas PGRI Palembang, 2016)
The objectives of this study are to provide empirical evidence about the influence of capital structure towards profitability. The analysis used independent variable of capital structure, and the independent variable proxied with Short-term Debt to asset (STD), Long-term Debt to asset (LTD), and Total Debt to asset (TDA). The dependent variable is profitability. Return on Equity (ROE) is used to measured profitability.Source of data used in this research was the secondary data derived from the Indonesian Stock Exchange data consiting of annual financial reports of LQ45 companies. The sample of companies used by 21 companies that issued LQ45 financial statements for the year 2011-2015. The methods analysis used in this research are descriptive analysis and multiple linear regresion.The results of research show that variables TDA does not have a significant relationship to profitability. While the STD and LTD variables have a significant relationship to profitability. STD Variable have a positive relationship to profitability.of LQ45 companies listed on Bursa Efek Indonesia over period 2011-2015. LTD Variable have a negative relationship to profitability.of LQ45 companies listed on Bursa Efek Indonesia over period 2011-2015 Keywords: Capital Structure, Profitability.